2009
DOI: 10.1056/nejmoa0808859
|View full text |Cite|
|
Sign up to set email alerts
|

Artemisinin Resistance inPlasmodium falciparumMalaria

Abstract: Please refer to usage guidelines at http://researchonline.lshtm.ac.uk/policies.html or alternatively contact researchonline@lshtm.ac.uk. Available under license: Copyright the publishersT h e ne w e ngl a nd jou r na l o f m e dic i ne n engl j med 361;5 nejm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
2,447
6
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 3,036 publications
(2,511 citation statements)
references
References 28 publications
41
2,447
6
17
Order By: Relevance
“…Cameroon with 71% of the total population living in hightransmission areas and 4500 deaths recorded annually is one of the most affected countries in Africa (WHO, 2014). The currently prescribed treatments particularly the Artemisinin-based Combination Therapies (ACTs) are threatened by emerging resistance of P. falciparum strains (Dondorp et al, 2009). Given these limitations, there is a motivated search for new drugs against Plasmodium parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Cameroon with 71% of the total population living in hightransmission areas and 4500 deaths recorded annually is one of the most affected countries in Africa (WHO, 2014). The currently prescribed treatments particularly the Artemisinin-based Combination Therapies (ACTs) are threatened by emerging resistance of P. falciparum strains (Dondorp et al, 2009). Given these limitations, there is a motivated search for new drugs against Plasmodium parasites.…”
Section: Introductionmentioning
confidence: 99%
“…artesunate is activated for the rest of intra-erythrocytic development, and thus, K13 variant parasites are fully susceptible to prolonged exposure to artemisinin, as clearly seen in vitro [2,4,5] and in vivo [3,22,23].…”
Section: Variants Of Pfk13 and The Parasite Cell Cycle In Vitromentioning
confidence: 95%
“…This was soon followed by more extensive observations from the randomised study of Dondorp et al [2]. Importantly, the latter study demonstrated that slow parasite clearance was observed in malaria patients from western Cambodia irrespective of whether they had been treated with monotherapy, or with artemisinin-based combination therapy (ACT), but this was not observed in patients from the Thailand-Myanmar border to the northwest.…”
Section: A New Artemisinin Susceptibility Phenotype Arises In Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…As the movement of both the malaria vector and parasite is not restricted by national boundaries regional drug pressure can influence drug efficacy within countries, as seen in KZN Province, SA [20] and Maputo Province, Mozambique. [37] Given the first-line antimalarial in all southern African countries is AL and that artemisinin resistance has been confirmed in Southeast Asia, [38] routine monitoring of AL efficacy is recommended, particularly in Limpopo Province, which currently experiences the highest incidence of African immigrant visitors.…”
Section: Regional Drug Pressurementioning
confidence: 99%